2017
DOI: 10.1055/s-0036-1593475
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular Reconstruction with Lateral Tibial Bone Graft: An Excellent Option for Oral and Maxillofacial Surgery

Abstract: Autogenous bone grafts are the gold standard for reconstruction of atrophic jaws, pseudoarthroses, alveolar clefts, orthognathic surgery, mandibular discontinuity, and augmentation of sinus maxillary. Bone graft can be harvested from iliac bone, calvarium, tibial bone, rib, and intraoral bone. Proximal tibia is a common donor site with few reported problems compared with other sites. The aim of this study was to evaluate the use of proximal tibia as a donor area for maxillofacial reconstructions, focusing on q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…Overall, 72% of the TBGs achieved successful bony union. Previous studies have reported success rates between 69% and 99% after orthognathic surgery or trauma‐related nonunion 12,27,33 . Our high success rates are reassuring given that our cohort had higher rates of radiation‐induced nonunion: 5%–11% previously reported compared to 67% of our patients underwent radiation after initial therapy 27,33 .…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Overall, 72% of the TBGs achieved successful bony union. Previous studies have reported success rates between 69% and 99% after orthognathic surgery or trauma‐related nonunion 12,27,33 . Our high success rates are reassuring given that our cohort had higher rates of radiation‐induced nonunion: 5%–11% previously reported compared to 67% of our patients underwent radiation after initial therapy 27,33 .…”
Section: Discussionsupporting
confidence: 68%
“…12,27,33 Our high success rates are reassuring given that our cohort had higher rates of radiationinduced nonunion: 5%-11% previously reported compared to 67% of our patients underwent radiation after initial therapy. 27,33 The only association with successful union was increased age. However, our small numbers would caution against any meaningful interpretation of this result.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Apart from the common post-operative surgical complications like infection, wound dehiscence, pain, gait disturbance, and paraesthesia, proximal tibia fractures have seldomly been reported in the literature [2] [51]. In a retrospective study by Ana Lucia et al on 31 patients who underwent tibial bone harvesting, only 5 cases of minor complications were noted which all self-resolved within three weeks [52]. Kushner reported a complication rate of just 1.4% in a series of 141 patients [49].…”
Section: Complicationsmentioning
confidence: 99%
“…It is also noted that the anatomy of the proximal tibia practically excludes the possibility of intra-operative complications. There is little information available about serious complications of the surgical procedure [ 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%